Unique microstructure and thermal insulation property of a novel waste-utilized foam ceramic. (1st July 2020) - Kuang, F.H.; Wang, S.M.; Gao, C.; Zhang, H.B.; Ren, R.K.; Ren, J.L.; Tong, J.; Liu, Y.M.; Liu, J.
Abstract: A characteristic CaO-Al2 O3 -SiO2 based foam ceramic was prepared by melt-foaming with solid wastes as main raw materials. The similarity to sandwich hole wall microstructure of this novel thermal insulating material was presented and the relationships between this unique microstructure and porosity, density, thermal conductivity and strength were discussed. Comparing the measured and theoretical values with that of the traditional foam ceramic, it can be found that, for the matching of fine skeleton with hole wall, this original sandwich structure can reduce thermal conductivity and increase flexural strength effectively.